2019
DOI: 10.1080/1828051x.2019.1596758
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate digestion and predicted glycemic index of bakery/confectionary ex-food intended for pig nutrition

Abstract: This study evaluated the predicted glycemic index (pGI) in former food products (FFPs), and in two pig compound feeds formulated with or without the inclusion of FFPs. Six samples of FFPs and two pig compound feeds were used. FFPs were based on bakery and confectionary exfood, while the pig compound feed was formulated by substituting 30% of cereals with FFPs (Feed FFP30%). All samples were analysed using an in vitro Englyst assay that simulates gastric and small intestinal digestion, and which has been propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Processing techniques (e.g., thermal processing, extrusion cooking etc.) are able to affect both digestibility and absorption of digested carbohydrates [13], which in turn have a major impact on the glycaemic index [10]. These dietetics features have been investigated by Ottoboni et al [13], who measured hydrolysis index (HI), predicted glycaemic index (pGI), and the time trend in carbohydrate digestion (k), in FFPs in comparison with common cereals.…”
Section: Former Food Products: Nutrient Content and Dieteticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Processing techniques (e.g., thermal processing, extrusion cooking etc.) are able to affect both digestibility and absorption of digested carbohydrates [13], which in turn have a major impact on the glycaemic index [10]. These dietetics features have been investigated by Ottoboni et al [13], who measured hydrolysis index (HI), predicted glycaemic index (pGI), and the time trend in carbohydrate digestion (k), in FFPs in comparison with common cereals.…”
Section: Former Food Products: Nutrient Content and Dieteticsmentioning
confidence: 99%
“…are able to affect both digestibility and absorption of digested carbohydrates [13], which in turn have a major impact on the glycaemic index [10]. These dietetics features have been investigated by Ottoboni et al [13], who measured hydrolysis index (HI), predicted glycaemic index (pGI), and the time trend in carbohydrate digestion (k), in FFPs in comparison with common cereals. Results obtained indicated that all parameters related to carbohydrate digestion (i.e., HI, pGI and k) were always higher in ex-food compared to conventional cereals feed ingredients such as unprocessed corn [13] (Figure 2).…”
Section: Former Food Products: Nutrient Content and Dieteticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A former foodstuffs producer based in the north of Italy has provided the complementary feed used for the formulation of the complete FFP diet. Based on our previous experience, the product with the highest in vitro digestibility (IVD) and the fastest carbohydrate digestion has been selected (Ottoboni et al 2019), given the nutritional needs of post-weaning piglets. The complementary feed was composed by, in descending order of inclusion: leftovers from the food industry (bakery products, pasta and confectionary products); wheat by-products (e.g.…”
Section: Former Food Evaluationmentioning
confidence: 99%
“…152/2009. Additional information on the pure FFP used in this study (namely FFP2) can be found in Giromini et al (2017) and Ottoboni et al (2019).…”
Section: Former Food Evaluationmentioning
confidence: 99%